2015
DOI: 10.1080/14786419.2015.1089243
|View full text |Cite
|
Sign up to set email alerts
|

Anticholinesterases and antioxidant alkamides from Piper nigrum fruits

Abstract: The anticholinesterase and antioxidant effects of five different extracts of Piper nigrum were evaluated. Twenty-one known alkamides were isolated from active ethyl acetate extract and investigated for their cholinesterase inhibitory and antioxidant effects. Among them, piperine (2), piperettine (5) and piperettyline (20) exhibited dual inhibition against AChE and BChE, and feruperine (18) was the most potent selective inhibitor of BChE. Molecular docking simulation was performed to get insight into the bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 15 publications
(14 reference statements)
0
12
0
2
Order By: Relevance
“…N -trans-feruloyltyramine could strongly suppress mRNA expression of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) via suppression of AP-1 and the JNK signaling pathway ( Jiang et al, 2015 ). Meanwhile, N -trans-feruloyltyramine exhibited the strongest DPPH radical-scavenging activity and cytotoxic effects against CCRF-CEM cell line with IC 50 values of 10.3 μg/mL ( Chen et al, 2015 ; Tu et al, 2016 ). Moreover, cannabisin F could successfully inhibit both ErbB1 and ErbB2, exhibiting better MolDock score than other selected inhibitors ( Hu et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…N -trans-feruloyltyramine could strongly suppress mRNA expression of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) via suppression of AP-1 and the JNK signaling pathway ( Jiang et al, 2015 ). Meanwhile, N -trans-feruloyltyramine exhibited the strongest DPPH radical-scavenging activity and cytotoxic effects against CCRF-CEM cell line with IC 50 values of 10.3 μg/mL ( Chen et al, 2015 ; Tu et al, 2016 ). Moreover, cannabisin F could successfully inhibit both ErbB1 and ErbB2, exhibiting better MolDock score than other selected inhibitors ( Hu et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Acetylcholine is degraded by AChE whose inhibition by AChE inhibitors is the most effective pharmacological approach for the symptomatic treatment of AD (Sorial and Sayed 2017;Weller 2018;Záborszky et al 2018;Zhang et al 2019). In the current study, the effect of treatments on AChE activity was not evaluated but we do not rule out the possibility that spilanthol, the compound we consider responsible for the plant's nootropic effects, has AChE inhibiting activity since it is reported that alkamides have such a property (Tu et al 2016).…”
Section: Discussionmentioning
confidence: 88%
“…As already reported, alkamides represent a class of natural compounds that are highly active in the CNS as they produce antinociceptive (Rios et al 2006;Gertsch et al 2008;Déciga-Campos et al 2010;Ong et al 2011;Das et al 2014), immunomodulatory (Gertsch 2008), anticholinesterases and antioxidant effects (Tu et al 2016). Previous studies suggest that these effects may be related to TRPV1 receptors modulation (Nomura et al 2013; de la Rosa-Lugo et al 2017).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Black pepper has been used in the Asian folk eISSN: 2550-2166 © 2020 The Authors. Published by Rynnye Lyan Resources MINI REVIEW medicine and the Indian Ayurvedic System of medicine folklore medicine of Latin America since many years ago (Tu et al, 2015). Pepper was also reported that it has been used in folk medicine to treat several ailments (Wan Salleh et al, 2014).…”
Section: Ethnomedicinal Uses Of Piperaceaementioning
confidence: 99%